Exploring the role of dance in architectural education - Daskalakos, C. (South African Journal of Higher Education, 2019)
The ‘dance_space’ project is an exploratory workshop with the objective to facilitate improved spatial design outcomes in first year architectural design students. In architecture, certain abstract spatial concepts are difficult to teach through the medium of language, which is less accessible to underprepared students and to sensory learners. The area of research is on using alternative pedagogies in spatial learning, looking at movement practice as a perceptual tool that can contribute to the development of spatial intelligence in architectural students with the objective to facilitate improved spatial design outcomes.